Pengembangan Media Pembelajaran Busy Book pada Materi Tema 6 Subtema 4 Kelas III di SD Negeri 10104481 Alur Baung T.A 2022/2023 - Nurafriani Dwi Agnesta; Laurensia Masri Perangin-Angin; Demmu Karo-Karo; Elvi Mailani; Husna Parluhutan Tambunan (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This study aims to determine the feasibility, practicality, and effectiveness of busy book learning media in learning themes 6 sub-themes 4 learning 1 class III at SD Negeri 10104481 Alur Baung, Karang Baru District, Aceh Tamiang Regency. This type of research is research and development using 4D mode by Thiagarajan. The instruments used were questionnaire validation sheets, test validation sheets, material expert validation sheets, media expert validation sheets, interview sheets, education specialist (teacher) questionnaires, as well as pre-test and post-test. The results of research related to feasibility show that the results of material experts give an average value of 86% which is categorized as "Very Eligible" and the results of media experts get an average value of 96% which is categorized as "Very Eligible". The results of research related to practicality show that the average value is 94% and is categorized as "Very Practical". While the results of research related to effectiveness to see student learning outcomes that the results of the pre-test trials showed that students completed only 4 students. Meanwhile, the results of the post-test trial showed that 30 students out of 30 students who completed the N-Gain score of 76% and were categorized as "Effective".